Silver Before Congress in 1886 - Horton, S. Dana (Quarterly Journal of Economics, 1886)
Journal Article Silver Before Congress in 1886 Get access S. Dana Horton S. Dana Horton Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 1, October 1886, Pages 45–75, https://doi.org/10.2307/1883108 Published: 01 October 1886